Induced-fit adsorption of diol-based porous organic polymers for tetracycline removal. (December 2018) - Zhang, Shenping; Li, Yankai; Shi, Chunhong; Guo, Fangyuan; He, Congze; Cao, Zan; Hu, Jun; Cui, Changzheng; Liu, Honglai
Abstract: Adsorption is recognized as one of the most efficient approaches for antibiotics removal from water. Inspired by the enzyme-substrate interaction model, we proposed induced-fit adsorption (IFA) model, and rationally designed and fabricated diol-based porous organic polymers (POPs) as adsorbents for tetracycline (TC) removal. For 2, 3-naphthalenediol-based POP (NTdiol-POP), the preferable geometry of diol-groups contributed to the high binding energy with TC species and flexible methylene linkages between neighboring rigid naphthalene rings gave rise to precisely matching between TC species and adsorbents, that is, the induced-fit conformation change. As a result, NTdiol-POP exhibited a high saturated adsorption capacity of 155.8 mg g −1 . More importantly, NTdiol-POP exhibited excellent TC removal efficiencies in both concentrated solution (96% for 4 p.p.m) and trace level solution (97% for 250 p.p.b). Graphical abstract: Highlights: Induced-fit Adsorption mechanism was proposed for antibiotics removal by POPs. Diol-based POPs with excellent porosity and dense active hydroxyl groups were tailored. Methylene groups among rigid network provided flexibility for conformation matching. Multi-hydrogen bonding induced the conformation change to enhance the adsorption. TC removal efficiency was about 97%, from 250 p.p.b to less than 5.5 p.p.b within 2 h.